Development of ionic liquid and lithium salt immobilized MCM-41 quasi solid-liquid electrolytes for lithium batteries. (February 2018) - Tripathi, Alok Kumar; Singh, Rajendra Kumar
Highlights: Li + -ion conducting quasi solid-liquid electrolytes (QS-LEs) based on solution of ionic liquid and lithium salt trapped into MCM-41 is prepared. QS-LE has high ionic conductivity, good Li + -ion transference number and high thermal stability. QS-LE displays outstanding electrochemical properties and battery performance with LiFePO4 cathode. Abstract: Li-ion conducting quasi solid-liquid electrolytes (QS-LEs) containing ionic liquid EMIMTFSI, lithium salt LiTFSI and ordered mesoporous MCM-41 (Mobil Composition of Matter no. 41) have been synthesized and characterized by N2 -sorption, SEM, TEM, DSC, TGA, and complex impedance spectroscopy techniques. The results show that the synthesized QS-LE has good thermal stability (∼360 °C; onset temperature) and a wide electrochemical window ∼5.23 V. The ionic conductivity is increases with increasing the amount of Li-IL (LIL) solution and attains a value of ∼6.37 × 10 −4  S cm −1 at 30 °C and 1.60 × 10 −3  S cm −1 at 70 °C for QS-LE containing high amount of LIL solution. The high ionic conductivity is attributed to the enormous adsorption of LIL solution on the external surface and in the ordered mesopores channels of the MCM-41. A high total ionic transference number (∼0.99) and cationic transference number (tLi +  ∼ 0.35) for QS-LE containing high amount of LIL solution have also been obtained. Furthermore, the QS-LE displays outstanding electrochemical properties (specific capacity ∼153 mAh g −1 at C/10 rate; and good high rate capability ∼100 mAh g −1 and 83 mAh g −1 at 1C and 2C rate respectively) and battery performance with LiFePO4 cathodes.